Density of Liquid Lead as Function of Temperature and Pressure Based on the Molecular Dynamics Method - Imanullah, Muhammad Abdul Bashar; Arkundato, Artoto; Purwandari, Endhah (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2018)
Simulation research has been carried out to obtain the formula for mass density of liquid lead as a function of temperature and pressure. The simulation method used is the molecular dynamics method. The potential energy used in the simulation is the Morse potential. From the simulation, it is found that the relationship between the mass density of liquid lead and temperature and pressure can be expressed in the equation pPb = 11233 - 0,9217 x T for pressure 1 – 5 atm and pPb = 11233 x 0,9213 x T for pressure 7 atm in units kg/m.